2007
DOI: 10.1103/physrevb.75.014114
|View full text |Cite
|
Sign up to set email alerts
|

Theory of low-energy electron diffraction for detailed structural determination of nanomaterials: Ordered structures

Abstract: To enable the determination of detailed structures of nanomaterials, we extend the theory of low-energy electron diffraction ͑LEED͒ to become more efficient for complex and disordered systems. Our new cluster approach speeds up the computation to scale as n log n, rather than the current n 3 or n 2 , with n the number of atoms, for example, making nanostructures accessible. Experimental methods to measure LEED data already exist or have been proposed. Potential application to ordered nanoparticles are illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…We briefly describe two computationally efficient methods to solve the multiple scattering problem in LEED [1][2][3]: an approximate grid-based method called Sparse-Matrix Canonical Grid or SMCG method; and the approximate "UV" method. Both approaches are iterative and rely in LEED on sufficient inelastic damping of electron wave amplitudes to compensate for the strong elastic scattering.…”
Section: Review Of the Nanoleed Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We briefly describe two computationally efficient methods to solve the multiple scattering problem in LEED [1][2][3]: an approximate grid-based method called Sparse-Matrix Canonical Grid or SMCG method; and the approximate "UV" method. Both approaches are iterative and rely in LEED on sufficient inelastic damping of electron wave amplitudes to compensate for the strong elastic scattering.…”
Section: Review Of the Nanoleed Methodsmentioning
confidence: 99%
“…SMCG outperforms UV for large numbers of atoms and large interatomic distances. But we also found that a more conventional approach, the Conjugate Gradient (CG) method [14], is more efficient than either SMCG or UV for small numbers of atoms and small interatomic distances [1][2][3]. Our NanoLEED code therefore combines these three methods and selects the most efficient one at each stage: a single structure often includes near, intermediate and distant neighbors, so different methods are applied to different pairs of atoms in the same structure.…”
Section: Review Of the Nanoleed Methodsmentioning
confidence: 99%
See 3 more Smart Citations